Kompetence k učení a možnosti jejího rozvíjení a hodnocení: vymezení pojmu a přehled současných přístupů. / Learning competencies and possibilities for their development and evaluation: Defining the concept and a review of current approaches. - Veronika Lokajíčková (Czech Pedagogical Society, 2013)
This theoretical study aims to provide an overview of knowledgeconcerning learning competencies and the possibilities for their development during instruction. The study is divided into two parts. The first one is concerned with defining the concept of learning competencies with regards to the concept of (key) competencies. Following selected authors, learning competencies are structured into(sub)dimensions, and so the approach to learning competencies as a multidimensional construct is highlighted. Further on, we point out how particular dimensions and (sub)dimensions are classified by selected authors, which brings further questionsregarding this construct. Three approaches to defining learning competencies are identified - definitions according to: (1) qualities - characteristics, (2) components - elements, and (3) combination of qualities and components (combined approach). In the second part of the study, four Czech approaches to developing learning competencies in the instruction are introduced. The